High Scool students’ reflective activity analyzed through its language oral manifestation - Falardeau, Érick; Simard, Denis; Sauvaire, Marion; Gagné, Julie-Christine (Swiss Journal of Educational Research, 2018)
This paper presents an analysis of the pedagogical practices of two French teachers to see how oral discussions in class reveal their students’ reflective activity. The purpose of this study originates from this question: What language manifestations of reflexive activity can we observe in teachers’ pedagogical practices that do not plan intentionally a reflective activity? This paper presents the theoretical and methodological tools that we have developed to describe and analyze students’ manifestations of the reflexive activity in oral discourses such as reformulation, explanation, comparison, argument, and creation.